Cancer prevalence in Israeli men and women with schizophrenia. (December 2017) - Agay, Nirit; Flaks-Manov, Natalie; Nitzan, Uri; Hoshen, Moshe B.; Levkovitz, Yeheal; Munitz, Hanan
Abstract: The aim of this cross–sectional study was to compare cancer prevalence rates among patients with schizophrenia to those of the non-schizophrenia population. The study population included members of Clalit Health Services aged 25 to 74 years and all data was taken from patients' electronic health records. Of the 2, 060, 314 members who were included in the study, 32, 748 had a diagnosis of schizophrenia. Cancer prevalence rates in women with and without schizophrenia were 491 per 10, 000 and 439 per 10, 000, respectively; in men, cancer prevalence rates were 226 per 10, 000 and 296 per 10, 000, respectively. The age-adjusted prevalence rate of all-type cancer was significantly lower among men with schizophrenia, compared to men without schizophrenia; specifically, men with schizophrenia had a lower rate of prostate cancer, and of cancers in the "other" category, compared to men without schizophrenia. Reduced cancer rates in men with schizophrenia may reflect under-diagnosis of some cancer types, likely due to insufficient medical attention. An effort to improve screening regimes should be made. Highlights: A large-scale cross–sectional study assessed cancer rates in schizophrenia. Cancer rates in people with schizophrenia and without schizophrenia were compared. Men with schizophrenia had lower rates of both all-type cancer and prostate cancer. In women, no significant differences in cancer rates were discovered.